Email system for the visually impaired - Sikula, Shingirai (Midlands State University, 2020)
The purpose of this project was to find and address the challenges faced by visually impaired persons when trying to communicate electronically. An emailing system was proposed and built. Email System for the visually impaired is a software system that aims to empower the blind and the visually impaired. It makes use of artificial cognitive intelligence to mimic human intelligence by converting user supplied voice message into text and then creating an email message to send to the desired recipient. Also, the software system is capable of reading aloud new mail and adding recipients to a local user directory. This intelligent behavior is powered by cloud based services that handles the Artificial Intelligence that processes the conversions from text to speech and vice versa. Research was done by interviewing people from the Jairos Jiri home and using various online sources to conduct a literature review that evaluates current systems and identifies gaps in these systems The information gathered was used to design the system and the design to implement the system. A speedy internet connection is recommended for this system to work smoothly.